Adsorption of Cs at the Hydroxyapatite/Aqueous Electrolyte Interface - E. Skwarek (Adsorption Science & Technology)
The aim of this paper is to discuss the changes in the double electrical layer at the hydroxyapatite/electrolyte solution interface during the adsorption of Cs + and to establish the relationship between the time and adsorption on this material. The adsorbent was prepared by wet precipitation methods, and characterized by X-ray diffraction and low-temperature nitrogen adsorption–desorption methods. The specific surface area of the adsorbent was characterized and the suitable particle sizes were determined. Adsorption of 137 Cs isotopes from ionic solutions was carried out at different concentrations and pH. The values of Cs + adsorption on the hydroxyapatite were quantified and the effect of Cs on its grains (particles) size, morphology, surface charge density and zeta potential was discussed.